Study of transpedicular screw fixation on spine development in a piglet model. Issue 1 (December 2016) - Shi, Ya-min; Zhu, Fang-zheng; Wei, Xing; Chen, Bing-yao
Abstract Background Transpedicular screws may cause damage to the cartilage in the neural arch of the vertebra, and give continuous pressure to the skeleton besides the vertebral body. The aim of this study is to examine the morphological change of the vertebral body at fixation sites and development of the vertebral body after fixation. Methods A piglet model was used to study the influence of transpedicular screw fixation on spine development. Transpedicular screw fixation was adjusted to meet specific requirements of surgery on piglet. The screws and plates were placed at L1–L3 vertebral plates via routine surgical approach. Scoliosis and kyphosis Cobb angles were measured. Results Anatomical characteristics of 6-week-old piglets fit the transpedicular screw system, and can meet the requirements of related studies. Transpedicular screw fixation system has no significant influence on the development of canalis vertebralis. Fixation did not cause developmental stenosis of canalis vertebralis and damage to spinal cord or nerve root. However, transpedicular screw fixation significantly impacted the development of the spine: it shortened the spine by curtailing the length of the vertebral body and intervertebral space. Our results also suggested that slow growth of epiphyseal plate may contribute to the shortening of the vertebral body. Conclusion Transpedicular screw fixation system is beneficial for fixation of the developing spine. It may not cause scoliosis but could lead to change of cervical curvature.